A Study of Property of Asphalt Concrete Mixture with Waste Plastic Bag - Satiennam, Thaned; Satiennam, Wichuda; Tankasem, Pongpan; Krongboon, Kittisak; Tamraksajaroen, Tanakit; Keereewong, Sarawut (Engineering and Applied Science Research, 2014)
The objective of this research is to study the property of the asphalt concrete mixture with used plastic bag. The laboratory test was performed by categorizing the mixing samplers into 2 groups; 1) asphalt concrete with various asphalt cement volumes (4%, 5%, 6%, 8% by mass of aggregate) and 2) asphalt concrete mixture with the waste plastic bag contents (4%, 6%, 8% by mass of mix). The total of mixing samplers was 39 samplers. The mixing samplers were prepared and tested in accordance with the Marshall method and the standard of Department of Highways. The study results show that the asphalt concrete mixing with waste plastic bag provided higher stability, lower density, and more volume but excessively higher air voids. It can be applied to construct the on-road surface traffic device that does not require high durability. It can save construction cost and the waste plastic bag can be reused.